A Hydrogen‐Bonded Ravel Assembled by Anion Coordination. (21st December 2021) - Zhao, Xiaotong; Wang, Heng; Li, Boyang; Zhang, Wenyao; Li, Xiaopeng; Zhao, Wei; Janiak, Christoph; Heard, Andrew W.; Yang, Xiao‐Juan; Wu, Biao
Abstract: Anion‐coordination‐driven assembly (ACDA) is showing increasing power in the construction of anionic supramolecular architectures. Herein, by expanding the anion centers from oxoanion (phosphate or sulfate) to organic tris‐carboxylates, an Archimedean solid (truncated tetrahedron) and a highly entangled, double‐walled tetrahedron featuring a ravel topology have been assembled with tris‐bis(urea) ligands. The results demonstrate the promising ability of tris‐carboxylates as new anion coordination centers in constructing novel topologies with increasing complexity and diversity compared to phosphate or sulfate ions on account of the modifiable size and easy functionalization character of these organic anions. Abstract : Anion‐coordination‐driven assembly (ACDA) between organic tris‐carboxylates and tris‐bis(urea) ligands afforded an Archimedean solid (truncated tetrahedron) and a double‐walled tetrahedron featuring a ravel topology. The results demonstrate the promising ability of tris‐carboxylates as new anion coordination centers in constructing novel topologies on account of the modifiable size and function of these organic anions.